2022
DOI: 10.3389/fimmu.2022.851004
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Long Non-Coding RNAs in the Tumor Immune Microenvironment

Abstract: Tumorigenesis is a complicated process caused by successive genetic and epigenetic alterations. The past decades demonstrated that the immune system affects tumorigenesis, tumor progression, and metastasis. Although increasing immunotherapies are revealed, only a tiny proportion of them are effective. Long non-coding RNAs (lncRNAs) are a class of single-stranded RNA molecules larger than 200 nucleotides and are essential in the molecular network of oncology and immunology. Increasing researches have focused on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 268 publications
(298 reference statements)
0
15
0
Order By: Relevance
“…Long non-coding RNA (lncRNA) and circular RNA (circRNA) are crucial types of ncRNAs that are sensitive to the tumor immune response. LncRNAs are involved in a variety of cellular processes and molecular signaling cascades via their modulation of PD-L1 expression at the epigenetic, transcriptional, and post-transcriptional levels [ 73 , 74 ]. Some circRNAs regulate the function of miRNAs as microRNA sponges and are essential to transcriptional regulation [ 75 ].…”
Section: Lncrna and Circrnamentioning
confidence: 99%
“…Long non-coding RNA (lncRNA) and circular RNA (circRNA) are crucial types of ncRNAs that are sensitive to the tumor immune response. LncRNAs are involved in a variety of cellular processes and molecular signaling cascades via their modulation of PD-L1 expression at the epigenetic, transcriptional, and post-transcriptional levels [ 73 , 74 ]. Some circRNAs regulate the function of miRNAs as microRNA sponges and are essential to transcriptional regulation [ 75 ].…”
Section: Lncrna and Circrnamentioning
confidence: 99%
“…Another mechanism through which hybrid E/M cancer cells induce immune evasion is related to the production of soluble factors. In particular, it has been reported that hybrid E/M cells upregulate the production of immunosuppressive mediators such as TGFβ, IL-8, IL-10, CSF1 (M-CSF), and CCL18 (Taki et al, 2018;Y. Guo, Xie, and Luo 2022) (Figure 4).…”
Section: Immunosuppressive Traits Of Hybrid E/m States and Immune Pla...mentioning
confidence: 99%
“…miRNAs are a group of non-coding RNA molecules with a length of 19–25 nucleotides that participate in the regulation of gene expression after transcription by targeting the 3untranslated region of the target mRNA sequence and inhibiting mRNA levels ( Navabi et al, 2022 ). lncRNAs are a class of single-stranded RNA molecules with more than 200 nucleotides that are important in molecular networks ( Guo et al, 2022 ). CircRNAs are a class of non-coding RNAs with high stability and significant clinical relevance ( Long et al, 2022 ).…”
Section: The Role Of Extracellular Vesicles-derived From Neurons/neur...mentioning
confidence: 99%